46, XY Disorders of Sexual Development: a case report and theoretical framework - Brambilla, Ilaria; Landi, Enrico; Guarracino, Carmen; Pistone, Carmelo; Tondina, Enrico; Sirchia, Fabio; Avolio, Luigi; Romano, Piero; Cavaiuolo, Silvia; Licari, Amelia; Riccipetitoni, Giovanna (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Disorders of sexual differentiation (DSD) with karyotype 46,XY include gonadal developmental differences such as complete gonadal dysgenesis, partial gonadal dysgenesis, testicular regression and ovotesticular sexual differentiation disorder, differences in androgen synthesis or action, such as androgen synthesis deficiency, androgen action deficits, LH receptor deficiency, AMH synthesis or action deficits, and other conditions such as severe hypospadias, cloaca estrophy, etc. Methods: A 17 years-old girl came to our attention for hirsutism, clitoral hypertrophy, primary amenorrhea, and bilateral mammary hypoplasia. According to clinical features and anamnesis, the diagnosis of 46, XY DSD was made. For diagnostic purposes, she underwent an extensive genetic analysis, hormone dosage and instrumental examinations. After a clitoridoplasty and hormone replacement treatment, the patient performs appropriate multidisciplinary follow-up and regular psychotherapy. Results: The clinical case reported falls, according to the recent classification developed by the Chicago Consensus, within the scope of DSD with karyotype 46, XY. About 160 cases of patients with 17β-HSD3 deficiency, diagnosed at a mean age of 12 years, are described in the literature, most of them coming from Western Asia and Europe and only three cases from Eastern Asia. Clinically, about 30% of patients showed virilization, 20% clitoromegaly, ambiguous genitalia, inguinal/labial mass, 16% primary amenorrhea, and 5% absence of mammary development, features that are partly traced in the case described here. Conclusions: This case underscores the complexity of managing individuals with DSD. Having acquired the concept that irreversible surgery should be avoided, except in cases where failure to do so would determine health risks, the primary objective of the medical decision lies in meeting conditions aimed at harmonious sexual identification, especially regarding sexual activity and fertility, involving a team of experienced professionals (psychologists, pediatricians, surgeons, endocrinologists, radiologists), capable of promptly identifying suggestive clinical signs.